Factors Predicting the Readiness of Village Health Volunteers for Screening and Prevention of Dementia in Community, Chonburi Province - Pholloka, Sukontip; Lawang, Wannaraty; Toonsiri, Chanandchidadussadee (Journal of The Royal Thai Army Nurses, 2024)
This predictive correlational research aimed to describe readiness and to determine factors predicting the readiness of Village Health Volunteers (VHVs) for screening and preventing dementia within the community. Multi-stage random sampling was used to recruit 192 VHVs within Chonburi province, who meet the specified criteria, data collection was using self-reports, including readiness questionnaires, consists of a readiness questionnaire Definition, Attitude and Social Support questionnaires (Cronbach’s alpha = 0.97, 0.89, 0.82, 0.93, respectively) and knowledge test (KR-20 = 0.73). Descriptive statistics and stepwise multiple regression statistics were performed to analyze the data. The study revealed that the overall readiness for screening and preventing dementia among VHVs was rated at a moderate level (M = 54.17, SD = 11.54, Madj = 3.01). By the meaning factor (β = 0.32, p<.05), social support (β = 0.20, p<.05), health status (β = 0.18, p<.05), and attitudes (β = 0.13, p<.05) could predict 30.6% of the variance accounted. (R2 = .306, R2adj = .292, F = 9.714, p<.05). These findings suggest that nurses and other health personnel who work in communities, should address for enhancing the readiness among VHVs, through preparedness program by focusing on promoting meaning of self and role, increasing attitudes towards dementia and role, taking care of health, including developing a health care and social support system for VHVs to lead to high performance of their roles and results.